Morphology and Molecular Characterization of Newly Isolated Microalgae Strain Chlorella volutis LIPI13-WKT066 from Wakatobi Islands and Its Potential Use - Rahman, Delicia Yunita; Praharyawan, Swastika; Fadiyah, Farizul; Raharjo, Sapto; Susilaningsih, Dwi (BRIN, 2019)
Morphology and molecular characterization of microalgae isolated from Wakatobi Marine National Park was conducted. An understanding of the characteristics of morphology, molecular, as well as metabolites profile of the microalgae species is potentially useful for its future application. The primary aim of this study was to isolate, identify and characterize the microalgae strain isolated from Wakatobi Marine National Park labeled as LIPI13-WKT066 with the emphasis on the evaluation of amino acid content as a basis for its health application. Morphological observation under the microscope and molecular identification suggested that the microalgae strain of LIPI13-WKT066 belong to the strain under species of Chlorella volutis. Metabolite characterization of the microalgae strain showed that the content of protein (11.9%), lipid (12.4%) and carbohydrate (4.7%) was in the regular range. Further analysis of its amino acid content revealed the potency of the microalgae strain to be used as antihypertensive agent.